META-ANALYTICAL EXAMINATION: UNRAVELING THE INTERPLAY BETWEEN PHYSICAL ACTIVITY AND CARDIOVASCULAR WELL-BEING IN A MULTIFACETED PARADIGM - Ns. Naziyah; Ahmadi; Rahmawati Dian Nurani; Loso Judijanto; Teguh Aprianto (Adisam Publisher, 2023)
This literature review delved into the intricate relationship between physical activity and cardiovascular health, employing a comprehensive meta-analytical approach. The introduction provided a contextual backdrop, emphasizing the significance of understanding this interplay. Methodologically, an extensive search strategy was implemented across reputable databases, guided by stringent inclusion and exclusion criteria. The data extraction process facilitated the meticulous collection of pertinent information, with a focus on critical variables. The meta-analysis revealed overarching themes and patterns, contributing to a nuanced understanding of the subject matter. The critical evaluation of selected studies offered insights into methodological strengths and limitations. In the discussion, findings were synthesized, developing a conceptual framework that synthesized various dimensions of the relationship between physical activity and cardiovascular health. The conclusion briefly summarized key findings, acknowledging the review's limitations and proposing avenues for future research.